2015
DOI: 10.1007/s10825-015-0708-y
|View full text |Cite
|
Sign up to set email alerts
|

Hankel transform domain analysis of covered circular microstrip patch printed on an anisotropic dielectric layer

Abstract: In the present paper, a rigorous full-wave analysis for determining the resonant frequency and half-power bandwidth of covered circular microstrip patch antenna is presented. Green's functions of the structure are determined in Hankel transform domain. Galerkin's is used in the resolution of the electric field integral equation. The TM set modes issued from the cavity model theory are used to expand to unknown current on the patch. For an isotropic substrate, it is demonstrated that the bandwidth decreases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The antenna parameters for this study are h = 1.27 mm. The computed resonant frequency in Verma [14] for various anisotropic substrates is also shown to agree very well with the values computed using cavity model (6)(7)(8)(9). The results of this comparison indicate that the present model shows excellent agreements with those of Verma [14] for all values of patch radius.…”
Section: Numerical Results and Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The antenna parameters for this study are h = 1.27 mm. The computed resonant frequency in Verma [14] for various anisotropic substrates is also shown to agree very well with the values computed using cavity model (6)(7)(8)(9). The results of this comparison indicate that the present model shows excellent agreements with those of Verma [14] for all values of patch radius.…”
Section: Numerical Results and Discussionsupporting
confidence: 72%
“…In a previously presented study [6][7][8], we have shown that circular microstrip antenna with the properly selected uniaxial anisotropic substrate is more advantageous the isotropic one by exhibiting wider bandwidth characteristic with different resonant frequencies. Several computational methods have been carried for computing the resonant characteristics of superconducting circular microstrip patch antenna by using the spectral domain analysis and other fullwave analysis methods [6,9]. With the increasing complexity of geometry and material property, designing these antennas requires more and more dedicated and sophisticated computer-aided-design (CAD) tools to predict the characteristics.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…When the thickness of the superconducting patch is less than three times of the zero-temperature penetration depth (λ 0 ), Z s can be expressed as follows [16][17][18][19]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Several researchers have studied the effect of the air gap layer on the resonant frequency of highTc superconducting microstrip patch antenna [7,10,13,17]. To the best of our knowledge, neither any design guideline nor any experimental or theoretical results are available in the open literature to predict the characteristics of high-Tc superconducting rectangular microstrip patch with substrate-superstrate configuration.…”
Section: Introductionmentioning
confidence: 99%